Sorry, wrong number [videorecording (DVD)] - Litvak, Anatole, 1902-1974; Stanwyck, Barbara, 1907-1990; Lancaster, Burt, 1913-1994; Richards, Ann, 1917-2006 (Paramount, 2002)
Young, rich, bedridden Barbara Stanwyck dials a telephone number one night and overhears two men plotting the murder of an unidentified woman. She becomes frantic. Her terror is intensified by mysterious calls from an old college rival and a friend of her father. With time running out, Stanwyck pieces evidence together that leads her to suspect that it is her husband who wants her murdered.